Conditioned Aversion and Neuroplasticity Induced by a Superagonist of Extrasynaptic GABAA Receptors: Correlation With Activation of the Oval BNST Neurons and CRF Mechanisms - de Miguel, Elena; Vekovischeva, Olga; Elsilä, Lauri V.; Panhelainen, Anne; Kankuri, Esko; Aitta-aho, Teemu; Korpi, Esa R. (Frontiers in Molecular Neuroscience, 2019)
THIP (gaboxadol), a superagonist of the delta subunit-containing extrasynaptic GABAA receptors, produces persistent neuroplasticity in dopamine (DA) neurons of the ventral tegmental area (VTA), similarly to rewarding drugs of abuse. However, unlike them THIP lacks abuse potential and induces conditioned place aversion in mice. The mechanism underlying the aversive effects of THIP remains elusive. Here, we show that mild aversive effects of THIP were detected 2 hours after administration likely reflecting an anxiety-like state with increased corticosterone release and with central recruitment of corticotropin-releasing factor CRF1 receptors. A detailed immunohistochemical c-Fos expression mapping for THIP-activated brain areas revealed a correlation between the activation of CRF-expressing neurons in the oval nucleus of the bed nuclei of stria terminalis and THIP-induced aversive effects. In addition, the neuroplasticity of mesolimbic DA system (24 hours after administration) and conditioned place aversion by THIP after 4 daily acute sessions were dependent on extrasynaptic GABAA receptors (abolished in delta-GABAA receptor knockout mice) and activation of the CRF1 receptors (abolished in wildtype mice by a CRF1 receptor antagonist). A selective THIP-induced activation of CRF-expressing neurons in the oval part of the bed nucleus of stria terminalis may constitute a novel mechanism for inducing plasticity in a population of VTA DA neurons and aversive behavioral states.